When do governments trade domestic reforms for external rewards? Explaining policy responses to the Millennium Challenge Corporation's eligibility standards. Issue 2 (13th December 2018) - Parks, Bradley C.; Davis, Caroline
Abstract : Journalistic reports and case study evidence suggest that governments have made policy and institutional reforms to achieve or maintain eligibility for assistance from the Millennium Challenge Corporation (MCC). However, the empirical scope of the "MCC Effect"—across countries, policy domains, and time—remains a subject of speculation and debate. There is also little rigorous evidence about the conditions under which the MCC eligibility standards have influenced the reform efforts of developing country governments. To address this challenge, we construct an original data set that measures whether, when, and how governments in low‐income and lower‐middle‐income countries responded to the eligibility requirements for MCC assistance between 2004 and 2010. Our econometric analysis of the data set calls attention to an underappreciated factor that shapes the adoption and implementation of externally influenced reforms: the presence of a technocratic reform team with executive authority to introduce disruptive changes to the status quo.